Efeitos do aumento de fluência do contato visual sobre a porcentagem de emissão, duração e latência desse comportamento em crianças com transtorno do espectro autista - Costa, Hiago Souza (Universidade Federal de São Carlos, 2026)
Reduced, absent, or atypical eye contact has been widely considered one of the indicators of Autism Spectrum Disorder (ASD). Beyond serving as a diagnostic marker, deficits in eye contact may lead to several difficulties throughout development, including limitations in social interactions and learning opportunities, impairments in joint attention, social referencing, and imitation, as well as delayed language development. Therefore, studies investigating effective procedures for teaching eye contact are needed. The present study aimed to apply an increased fluency teaching procedure and evaluate its effects on the percentage, latency, and duration of this response. A nonconcurrent multiple baseline design was employed. Five children with ASD, receiving services at a private clinic, participated in the study. The procedure consisted of six phases: preference assessment, baseline, eye contact teaching, return to baseline conditions, generalization, and maintenance. The results indicated that the procedure was effective in increased fluency of eye contact for all participants, with increases in response percentage and duration and reductions in latency. Performance was also maintained under conditions without programmed reinforcement and generalized to contexts different from the teaching environment. It is concluded that the investigated procedure represents a promising strategy for teaching eye contact, potentially supporting the development of attentional repertoires relevant to learning and social interaction.
Effects of increased eye contact fluency on the percentage of eye contact responses, duration, and latency in children with autism spectrum disorder
Keywords: Contato visual; Autismo; Intervenção; Reforço diferencial; Fluência; CIENCIAS HUMANAS::PSICOLOGIA; 3. Saúde e Bem-Estar